INFLUENCE OF CYTOMEGALOVIRUSES ON FETAL DEVELOPMENT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article analyzes the effect of cytomegalovirus (CMV) infection on fetal development, its pathogenesis, clinical manifestations and preventive measures. Cytomegalovirus is a DNA virus belonging to the herpesvirus family, which is latent in most people and is activated in conditions of weakened immune systems. The development of primary or recurrent CMV infection in a pregnant woman can cause intrauterine infection. The article discusses the mechanisms of virus transmission to the fetus through the placenta, as well as morphological and functional changes in embryonic and fetoplacental development. CMV-infected fetuses are mainly characterized by pathologies such as central nervous system damage, developmental defects of the hearing and vision organs, microcephaly, and intrauterine growth retardation. The article also presents diagnostic methods (serological tests, PCR), preventive and therapeutic measures, and recommendations for preventing CMV infection during pregnancy. The results of the study indicate the need for early detection and monitoring of CMV infection in pregnant women.